Pensar el conflicto político en la democracia : un diálogo entre Miguel Abensour y Karl Marx (2017)
"This thesis discusses on the theoretical implications to think the political conflict in a democracy. The study focuses on a dialog between two philosophers of different times: Miguel Abensour and Karl Marx. On the one hand, Abensour state the need to think the political conflict from democracy and emancipation, with a clear commitment for the historical contingency. On the other hand, Marx thinks the political conflict also from the emancipation, but concerned to the historicity of this concept. In his case, the consequence is to articulate his argument with the concept of class struggle, which involve contradictions with multiple interpretations." -- Tomado del Formato de Documento de Grado.